Design, Implementation, and Performance of CREAM Data Acquisition Software - Zinn, S Y; Ahn, H S; Bagliesi, M G; Beatty, J J; Childers, J T; Coutu, S; Duvernois, M A; Ganel, O; Kim, H J; Lee, M H; Lutz, L; Malinine, A; et al. (2005)
Cosmic Ray Energetics and Mass (CREAM) is a balloon-borne experiment scheduled for launching from Antarctica in late 2004. Its aim is to measure the energy spectrum and composition of cosmic rays from proton to iron nuclei at ultra high energies from 1 to 1,000 TeV. Ultra long duration balloons are expected to fly about 100 days. One special feature of the CREAM data acquisition software (CDAQ) is the telemetric operation of the instrument using satellites. During a flight the science event and housekeeping data are sent from the instrument to a ground facility. Likewise, commands for controlling both the hardware and the software are uploaded from the ground facility. This requires a robust, reliable, and fast software system. CDAQ has been developed and tested during three beam tests at CERN in July, September, and November 2003. Recently the interfaces to the transition radiation detector (TRD) and to the timing-based charge detector (TCD) have been added. These new additions to CDAQ will be checked at a thermal/vacuum test of the instrument at NASA. The design, implementation, and performance of CDAQ are reported.